BALANCING ACT: Effective Stress Management For A Harmonious Work Environment. Elevate Your Workday, Stress Less Achieve More! - Ade Nurhasanah; Ihsan Ihsan; Lili Karmela Fitriani (Journal Of Social Science (JoSS), 2024)
In today's fast-paced and dynamic work environment, stress management is key to creating a harmonious and productive workplace. Workplace stress is not only a challenge but also an opportunity to improve personal well-being and professionalism. This research aims to explore practical and proven stress management strategies that can improve the quality of the workday and work outcomes. Based on the Systematic Literature Review (SLR), practices such as mindfulness and programs such as Mindfulness-Based Stress Reduction (MBSR) are proven to reduce emotional exhaustion and improve employees' psychological well-being. In addition to individual stress management, these strategies also positively impact team dynamics by reducing interpersonal conflict and encouraging collaboration. However, implementation of stress management practices in the workplace often faces barriers such as resistance to cultural change and insufficient support from management. Overcoming these barriers requires a comprehensive approach that involves education, training, and the development of supportive policies. An organizational culture that prioritizes mental health and leadership that emphasizes employee well-being is critical to the long-term success of workplace stress management techniques. By integrating these strategies, this research aims to empower individuals and organizations to control stress, increase job satisfaction, and achieve professional goals more effectively.